Features and differences of the European system of human rights from other legal mechanisms (Journal of actual problems of jurisprudence, 2022)
The purpose of this article is to highlight the role of the European human rights system in the protection of human rights and fundamental freedoms. Accordingly, the authors determine its place in the system of protection of human rights and fundamental freedoms by comparing the EU Charter of Fundamental Rights, the European Convention on Human Rights and Fundamental Freedoms of 1950, the European Social Charter and OSCE documents. The article reveals the special role of these normative acts in the protection of human rights and freedoms in general. Within the framework of the topic, the normative legal acts on human rights in circulation were interconnected to analyze the work in the legal context for implementation into the legal system. Relevant articles are provided as examples. The article emphasizes the importance of the European system of human rights protection for the law enforcement activities of the Republic of Kazakhstan. The regulatory framework of the European legal space in this area has been comprehensively analyzed. Based on the results of the study, it was proposed to include effective parts of the European system of human rights protection in the domestic system of human rights protection. For the mechanism of realization of human and civil rights, under the current legislation we understand a system of methods and means of realization of a particular right, organized in a functional and chronological order.Keywords: human rights and freedoms, European Convention, charter, fundamental rights, protection of human rights, mechanism, system.